Heartbeat Cycle Length Detection by a Ballistocardiographic Sensor in Atrial Fibrillation and Sinus Rhythm. (1st July 2015) - Zink, Matthias Daniel; Brüser, Christoph; Winnersbach, Patrick; Napp, Andreas; Leonhardt, Steffen; Marx, Nikolaus; Schauerte, Patrick; Mischke, Karl
Abstract : Background. Heart rate monitoring is especially interesting in patients with atrial fibrillation (AF) and is routinely performed by ECG. A ballistocardiography (BCG) foil is an unobtrusive sensor for mechanical vibrations. We tested the correlation of heartbeat cycle length detection by a novel algorithm for a BCG foil to an ECG in AF and sinus rhythm (SR). Methods. In 22 patients we obtained BCG and synchronized ECG recordings before and after cardioversion and examined the correlation between heartbeat characteristics. Results. We analyzed a total of 4317 heartbeats during AF and 2445 during SR with a correlation between ECG and BCG during AF of r = 0.70 (95% CI 0.68–0.71, P < 0.0001 ) and r = 0.75 (95% CI 0.73–0.77, P < 0.0001 ) during SR. By adding a quality index, artifacts could be reduced and the correlation increased for AF to 0.76 (95% CI 0.74–0.77, P < 0.0001, n = 3468 ) and for SR to 0.85 (95% CI 0.83–0.86, P < 0.0001, n = 2176 ). Conclusion. Heartbeat cycle length measurement by our novel algorithm for BCG foil is feasible during SR and AF, offering new possibilities of unobtrusive heart rate monitoring. This trial is registered with IRB registration number EK205/11. This trial is registered with clinical trials registration number NCT01779674 .